Autoantibodies and the Hepatitis-associated Antigen in Acute Infective Hepatitis. Issue 5711 (20th June 1970) - Farrow, L. J.; Holborow, E. J.; Johnson, G. D.; Lamb, S. G.; Stewart, J. S.; Taylor, P. E.; Zuckerman, A. J.
Abstract : In 39 unselected patients with acute infective hepatitis diagnosed on clinical, epidemiological, and pathological findings, smooth muscle (S.M.) antibody was found in 87% and hepatitis-associated antigen in 33%. The incidence of S.M. antibody was highest during the first month after the onset of symptoms, and the antibody was preponderantly IgM at this stage. S.M. antibody and hepatitis-associated antigen occurred independently, and unlike hepatitis-associated antigen, which was strongly associated with possible parenteral exposure to infection, the incidence of S.M. antibody was not related to the presumed mode of exposure. It is concluded that production of S.M. antibody is more directly related to liver cell damage than to the presence of hepatitis-associated antigen in the serum.